A Cytotoxic Indole Characterized by Incorporation of a Unique Carbon–Nitrogen Skeleton and Two Pentacyclic Corynanthean Alkaloids Incorporating a Substituted Tetrahydrofuranone Ring from Kopsia arborea - Wong, Soon Kit; Wong, Suet Pick; Sim, Kae Shin; Lim, Siew Huah; Low, Yun Yee; Kam, Toh Seok (American Chemical Society, 2019)
Three new alkaloids were isolated from the bark extract of the Malayan Kopsia arborea, viz., arbophyllidine (1), an unusual pentacyclic, monoterpenoid indole characterized by an absence of oxygen atoms and incorporating a new carbon-nitrogen skeleton, and arbophyllinines A (2) and B (3), two pentacyclic corynanthean alkaloids incorporating a hydroxyethyl-substituted tetrahydrofuranone ring. The structures of the alkaloids were deduced based on analysis of the MS and NMR data and confirmed by X-ray diffraction analyses. The absolute configuration of arbophyllidine (1) was established based on experimental and calculated ECD data, while that of arbophyllinine A was based on X-ray diffraction analysis (Cu Kα). A reasonable biosynthetic route to arbophyllidine (1) from a pericine precursor is presented. Arbophyllidine (1) showed pronounced in vitro growth inhibitory activity against the HT-29 human cancer cell line with IC50 6.2 μM. © 2019 American Chemical Society and American Society of Pharmacognosy.